Implementation of Single-Walled Carbon Nanohorns into Solar Cell Schemes - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (Advanced Energy Materials, 2017)
Recent advances in dye-sensitized solar cells (DSSC), including the use of nanocarbons, resulted in breakthroughs relevant to both the academic and industrial sectors. Their relevance encompasses, on one hand, the development and integration of novel nanocarbon/dye hybrids for superior light-harvesting and improved charge injection properties and, on the other hand, the integration of nanocarbons into each part of DSSCs for enhancing the charge collection efficiency as well as the dye and electrolyte regeneration processes. In the context of the earlier, control over the electron injection and recombination rates is realized on the molecular level. In the context of the latter, i) the charge transport and charge collection efficiencies in the photoelectrode are increased, ii) the charge recombination processes are reduced, when used as a nanocarbon-based buffer layer, iii) the ion diffusion and catalytic effects into (quasi) solid-state electrolytes are improved, and iv) devices using Pt-free counter electrodes with similar device efficiencies are realized. Leading examples of nanocarbons are graphene, carbon black, multi-walled carbon nanotubes, and single-walled carbon nanotubes. In this review, the focus is on a novel carbon allotrope, namely single-walled carbon nanohorns (SWCNH), which is discussed in depth and in comparison with other nanocarbons.
EAM Import::2019-03-13